Central nervous and cardiovascular effects of i.v. infusions of ropivacaine, bupivacaine and placebo in volunteers - Knudsen, K; Beckman Suurküla, M; Blomberg, S; Sjövall, J; Edvardsson, N (British journal of anaesthesia : BJA, 1997)
We have compared the incidence of CNS symptoms and changes in echocardiography and electrophysiology during i.v. infusions of ropivacaine, bupivacaine and placebo. Acute tolerance of i.v. infusion of 10 mg min-1 was studied in a crossover, randomized, double-blind study in 12 volunteers previously acquainted with the CNS effects of lignocaine. The maximum tolerated dose for CNS symptoms was higher after ropivacaine in nine of 12 subjects and higher after bupivacaine in three subjects. The 95% confidence limits for the difference in mean dose between ropivacaine and bupivacaine were -30 and 7 mg. The maximum tolerated unbound arterial plasma concentration was twice as high after ropivacaine (P < 0.001). Muscular twitching occurred more frequently after bupivacaine (P < 0.05). The time to disappearance of all symptoms was shorter after ropivacaine (P < 0.05). A threshold for CNS toxicity was apparent at a mean free plasma concentration of approximately 0.6 mg litre-1 for ropivacaine and 0.3 mg litre-1 for bupivacaine. Bupivacaine increased QRS width during sinus rhythm compared with placebo (P < 0.001) and ropivacaine (P < 0.01). Bupivacaine reduced both left ventricular systolic and diastolic function compared with placebo (P < 0.05 and P < 0.01, respectively), while ropivacaine reduced only systolic function (P < 0.01).